The Role of Bankruptcy Fraud in Financial Crimes - Akbarkhon Azamov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Bankruptcy fraud is a significant financial crime that extends beyond mere insolvency misrepresentation. It serves as a mechanism for broader economic offences such as money laundering, tax evasion, and corporate fraud. This article examines the various forms of bankruptcy fraud, including asset concealment, fraudulent transfers, and false declarations. It explores its implications on the financial system, regulatory challenges, and legal frameworks across jurisdictions. By analysing notable case studies, this article highlights the sophisticated methods used to exploit bankruptcy laws and discusses preventive measures, enforcement strategies, and the role of international cooperation in mitigating this crime.